2019
DOI: 10.1055/a-0839-4312
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound findings and pathological features of pancreatic carcinoma in situ

Abstract: Background and study aims Few studies have evaluated detection of pancreatic carcinoma in situ (PCIS). We evaluated findings of endoscopic ultrasound (EUS) and pathological features of PCIS. Patients and methods We histopathologically studied 16 patients with PCIS following EUS. Diagnostic features evaluated retrospectively included stricture of the main pancreatic duct (MPD) on EUS, presence or absence of hypoechoic areas surrounding the MPD stricture on EUS, the noncancerous part (pancreas of backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 24 publications
(25 reference statements)
0
44
0
Order By: Relevance
“…Izumi et al reported that a hypoechoic area surrounding the MPD stenosis was detected in 56.3% of PCIS, and fatty infiltration was detected in 43.8% of PCIS. They also reported that histopathological examination of the periphery of the lesion revealed inflammation and fibrosis in all PCIS [ 35 ]. It is conceivable that the hypoechoic lesion could reflect the fibrosis ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Izumi et al reported that a hypoechoic area surrounding the MPD stenosis was detected in 56.3% of PCIS, and fatty infiltration was detected in 43.8% of PCIS. They also reported that histopathological examination of the periphery of the lesion revealed inflammation and fibrosis in all PCIS [ 35 ]. It is conceivable that the hypoechoic lesion could reflect the fibrosis ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two diagnostic approaches are available for PC, EUS-fine needle aspiration (FNA), and Serial pancreatic juice aspiration cytologic examination (SPACE). EUS is powerful detection tool for PC ≤ 20 mm in size [ 4 , 5 ] and specific EUS findings in patients with small PCs was recently reported [ 27 , 28 ]. Additionally, EUS-FNA has been widely used for pathological confirmation due to high sensitivity and specificity [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of EUS for tumor detection was 92.4%, whereas transcutaneous ultrasonography (TUS), CT, and MRI had a sensitivity of only 67.3%, 65.8%, and 57.5%, respectively [33]. Other studies using TUS and EUS have highlighted the high diagnostic value of these techniques for the detection of MPD dilatation or stricture in order to diagnose small PDACs [34][35][36]. The unmatched diagnostic ability of EUS was also described for the detection of pancreatic neuroendocrine tumors (PNETs).…”
mentioning
confidence: 99%